Improving the light curves of gravitationally lensed quasars with Gaia proper motion data - Sorgenfrei, Christian Matthias; Schmidt, Robert W.; Wambsganß, Joachim (Astronomy and astrophysics, 2024)
Aims. We show how to significantly improve difference image analysis (DIA) of gravitationally lensed quasars over long periods of time using Gαία proper motions. Methods. DIA requires the subtraction of a reference image from the individual images of a monitoring campaign, using stars in the field to align the images. Since the proper motion of the stars can be of the same order as the pixel size during a several-year campaign, we use Gaia DR3 proper motions to enable a correct image alignment. The proper motion corrected star positions can be aligned by the ISIS package. DIA is carried out using the HOTPAnTS package. We apply point spread function (PSF) photometry to obtain light curves and add a proper motion correction of the PSF star to GALFIT. Results. We apply our method to the light curves of the three gravitationally lensed quasars HE1104-1805, HE2149-2745 and Q2237+0305 in the R and V band, respectively, obtained using 1 m telescopes of the Las Cumbres Observatory from 2014 to 2022. We show that the image alignment and the determination of the lensed quasar positions is significantly improved by this method. The light curves of individual quasar images display intrinsic quasar variations and are affected by chromatic microlensing.
Gesehen am 26.07.2024